Folklore and Identity in Dracula - Harney, Michael (2013)
Bram Stoker's Dracula employs certain folkloric motifs to express a set of themes grouped under the heading of hegemonic angst. In Stoker's tale of reverse imperialism, the vampiric invader, in a kind of carnivalesque inversion, plays the role of the historical Cortés or the Quijote's captive. Dracula's chief victims, Lucy and Mina, remind us of La Malinche, Cervantes's Zoraida, and other ancient and medieval examples of the sequestered native princess.